MANUBRIOSTERNAL JOINT INVOLVEMENT IN PSORIATIC ARTHRITIS - Hassan Iffat; Yaseen Ummar; Ahmad Mashkoor; Masood Qazi (Our Dermatology Online, 2011)
Psoriatic arthritis (PsA) is a type of seronegative arthiritis associated with psoriasis of skin and nails. It affects axial and eripheral joints with variable severity. The course and prognosis of the disease suggest that early diagnosis and aggressive treatment are important. The most common clinical type of PsA is oligoarthiritis in which four or fewer joints are involved often in an asymmetrical pattern, and arthritis mutilans which is the destructive form and is the least common. We report a case of PsA in which the manubriosternal joint alone was involved as initial manifestation in association with psoriatic erythroderma.